Pulmonary Hypertension and Its Determinants in β-thalassemia Major and Intermedia Considering Left Ventricular Functional State - Behzad Farahani; Abbas Fadaii; Isa Khaheshi; Forooz Baktash; Mohammad Amin Abbasi; Ronak Mohammadi; Koosha Paydary (International Journal of Cardiovascular Practice, 2016)
Introduction: Pulmonary hypertension (PHT) is a common complication in β-thalassemia. We aimed to determine the prevalence of PHT and its main indicators in patients with β thalassemia Major (TM) and β-thalassemia Intermedia (TI), considering left ventricular function.Methods: Pulmonary hypertension (PHT) is a common complication in β-thalassemia. We aimed to determine the prevalence of PHT and its main indicators in patients with β thalassemia Major (TM) and β-thalassemia Intermedia (TI), considering left ventricular function.Results: The overall prevalence of PHT in TM and TI group was estimated to be 35.2% and 29.3%, respectively; while reduced LVEF was evident in 22.7% and 10.1% of patients with TM and TI, respectively. No significant correlation was observed between mean PAP and LVEF in the patients with TI (Pearson coefficient = -0.096, P value = 0.345); while, an adverse association was revealed between mean PAP and LVEF in patients with TM (Pearson coefficient = -0.227, P value = 0.033). Upon univariate analysis, the only significant association was observed between LVEF and pulmonary hypertension among TM patients (P value = 0.001).Our results did not indicate that male gender and aging may affect the development of PHT.Conclusions: According to our findings, a considerable proportion of patients with TM and TI may have PHT. We detected an adverse association between mean PAP and LVEF in patients with TM. Left ventricular function was reduced in patients with PHT among TM group.